From Possibility to Action: An Interdisciplinary Action-Learning School dealing with Waste - Lambert-Pennington, Katherine; Saija, Laura; Franchina, Alice (Cambio. Rivista sulle Trasformazioni Sociali, 2018)
For more than a decade, researchers and activists have collaborated in the Simeto Valley for the advancement of development inspired by social solidarity and the need of reconnecting people to the local ecosystem. Over time, this experiment has progressively turned into an interdisciplinary action research partnership that involves now mainly planners and anthropologists. One of the activities carried out in the Valley is an action-learning Summer School organized by the University of Memphis in partnership with the University of Massachussets, Boston and the University of Catania. The work of this partnership lies between planning and anthropology and has generated an interdisciplinary space and a shared methodology of action-learning. This methodology is neither exclusively inductive nor used as a basis for deduction, but modified in the course of collective action. This paper describes the theoretical and pedagogical principles underlying CoPED and draws on its 2017 edition, which focused on Zero Waste, to show how it provides a platform for theory-in-action.